Green Consumers: a growing market for SME’s and a paradigm shift from eco-entrepreneurship to social entrepreneurship. - Naila Aaijaz; Mohamed Dahlan Ibrahim (2009)
Every entrepreneur and marketer knows that material goods and services serve multiple purposes to consumers. Purpose is to satisfy basic needs such as subsistence and protection. In the last two decades consumers have become more environment and health conscious. The trend has led to more independent businesses and entrepreneurial ventures focused towards green consumers. In food products, the environmental friendly food is termed as “Organic” food and is considered healthy (Chinnici et. al, 2002).